Geochemical Characteristics and Origin of Shale Gases From Sichuan Basin, China - Ni, Yunyan; Dong, Dazhong; Yao, Limiao; Chen, Jianping; Liang, Xing; Liu, Fei; Li, Jian; Guo, Jinhao; Gao, Jinliang (Frontiers in Earth Science, 2022)
Natural gases from the Taiyang (shallow), Jiaoshiba (middle) and Weirong (deep) shale gas fields in the southern Sichuan Basin were analyzed for molecular and stable carbon isotopic compositions to investigate the geochemical characteristics and gas origins. All the gases belong to shale gas from the Upper Ordovician-Lower Silurian shale, and are dominated by methane with gas wetness generally less than 0.83%. The δ13C1 values are -28.5‰, -30.3‰ and -35.2‰ in Taiyang, Jiaoshiba and Weirong shale gas fields, respectively. The extremely high thermal maturity is the controlling factor for the enrichment of 13C in methane, with minor contribution from the heavy carbon isotope of the organic matter in the Ordovician Wufeng Formation. Fischer-Tropsch-type synthesis of hydrocarbon gas from CO2 and H2 contributes to the increase of wet gas, which result in the offset from the δ13C1~wetness linear trend in the Taiyang and Jiaoshiba gas fields. Methane, ethane and propane in Taiyang shale gas field have increasing δ13C values with increasing burial depth, which is mainly caused by diffusive migration. All gases are characterized by complete carbon isotopic reversal trend (δ13C1>δ13C2>δ13C3), and it is mainly caused by the reversible free radical reactions with conversion from alkane to alkyl groups, with some contribution from the Fischer-Tropsch-type synthesis. The results in this study will improve our understanding of the geochemical characteristics of shale gases from different burial depths and have important implications for future shale gas exploration in the deep and shallow layers.